Humour and Knowledge in Katherine Mansfield’s “The Daughters of the Late Colonel” (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
In recent times, Bollywood comedies have evidenced a shift in their attitude and perspective towards body image. In earlier comedies, people of different physical appearances were stigmatized. That approach has changed of late and as a result, these movies now serve as powerful catalysts for positive change in society. This article offers an overview of the transformative role played by Bollywood comedy films in contributing to body positivity and promoting self-acceptance. Through an analysis of a selection of films such as Bala (2019), Dum Laga Ke Haisha (2015), and Gippi (2013), this study explores how these movies influence individuals’ perceptions, destigmatize identity, challenge stereotypes, and advocate for self-acceptance. This study also emphasizes the role of humour as a central element to engage audiences in sensitive discussions surrounding body image. In a nutshell, this research highlights the profound impact of comedy films on individuals and how these films reshape societal perceptions from body shaming to body acceptance.